A direct measurement of wall shear stress in multiphase flow—Is it an important parameter in CO2 corrosion of carbon steel pipelines?. (September 2016) - Li, Wei; Pots, B.F.M.; Brown, Bruce; Kee, Kok Eng; Nesic, Srdjan
Highlights: Wall shear stress in multiphase flow was directly measured using a floating element method instead of deploying less reliable indirect measurement methods used in the past. The highest wall shear stress measured was of the order of 100 Pa. It was calculated that in the field the value would not exceed 1000 Pa. This value of wall shear stress is much lower than the required mechanical stresses to remove protective corrosion inhibitor films. Abstract: Wall shear stress produced by turbulent multiphase flow is considered an important parameter in CO2 corrosion as it has been claimed to be responsible for the removal of protective corrosion product layers and corrosion inhibitor films. In this study, a floating element wall probe was used to directly measure wall shear stress in multiphase flow; the highest measured values were of the order of 100 Pa. Findings suggest that the wall shear stress alone, produced in multiphase flow patterns covered in the present study, is insufficient to mechanically damage the protective corrosion product layers or corrosion inhibitor films.